Casuística de ambiguidade genital em hospital público universitário - Camila Clemente Luz; Isabel Rey Madeira; Daniel Luis Schueftan Gilban; Ana Paula Neves Bordallo; Paulo Ferrez Collett Solberg; Clarice Borschiver de Medeiros; Fernanda Mussi Gazolla; Claudia Braga Monteiro; Ana Carolina dos Santos Carvalho; Renata Mota Vieira guerreiro (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: Ambiguous genitalia is a disorder of sex development. Incidence has been estimated at approximately one in 4,500-5,500 live births. The investigation and diagnosis of ambiguous genitalia is a clinical emergency given the importance of detecting life-threatening conditions such as congenital adrenal hyperplasia and malformation syndromes early on. METHOD: This cross-sectional observational study included 56 medical charts of patients referred to the Pediatric Endocrinology Department of a public university hospital. RESULTS: Congenital adrenal hyperplasia was the most common disease with 11 cases (19.5%), followed by partial androgen insensitivity syndrome with eight cases (14.2%), Klinefelter syndrome with five cases, and mixed gonadal dysgenesis with four cases. Patient mean age at first visit was 55 months. Family history, gestational history, gonadal characteristics, and treatment were also analyzed. CONCLUSION: The identification and management of children and adolescents with ambiguous genitalia must be carefully executed by a multidisciplinary team with experience on the subject. The repercussions of late diagnosis or inadequate case management cannot me measured, but affect the way patients relate to themselves and society around them.